Reliability and Validity of the American Heart Association's Workplace Health Achievement Index. Issue 1 (January 2022) - Roemer, Enid Chung; Kent, Karen B.; Goetzel, Ron Z.; Calitz, Chris; Mills, Drew
Objective: To test the validity and reliability of the American Heart Association's (AHA) updated Workplace Health Achievement Index (WHAI). Methods: We piloted the updated WHAI with respondent pairs at 94 organizations, and examined the inter-rater reliability (percent agreement) for each item on the survey. To evaluate face and content validity, we conducted preliminary focus groups pre-survey, and follow-up cognitive interviews post-survey administration. Results: Respondents found the updated WHAI to be comprehensive and useful in identifying gaps and opportunities for improving their health and wellbeing programs. The mean percent agreement on all items was 73.1%. Only 9% (or 14 items out of 146) had poor inter-rater reliability (below 61 percent agreement), but through follow-up cognitive interviews we determined that most were due to artifacts of the study design or were resolved through minor revisions to the survey question, instructions, and/or adding examples for clarity. Only 1 question was deleted due to lack of relevance. Conclusion: The updated WHAI is a valid and reliable tool for employers to assess how well they promote the health and wellbeing of their employees.